Psychometric properties of the self-report version of the Quick Inventory of Depressive Symptoms (QIDS-SR(16)) questionnaire in patients with schizophrenia - Lako, Irene M (BioMed Central, 2014)
BACKGROUND: Self-report instruments for the assessment of depressive symptoms in patients with psychotic disorders are scarce. The Quick Inventory of Depressive Symptoms (QIDS-SR(16)) may be a useful self-report instrument, but has received little attention in this field. This paper aimed to test the psychometric properties of the QIDS-SR(16) questionnaire in patients with a psychotic disorder. METHODS: Patients diagnosed with a psychotic disorder from health care institutions in The Netherlands were included in the study. Depressive symptoms were assessed with the QIDS-SR(16) and the Calgary Depression Scale for Schizophrenia (CDSS). Psychotic symptoms were assessed with the Positive and Negative Syndrome Scale (PANSS) and extrapyramidal symptoms (EPS) with three EPS rating scales. Spearman’s correlation coefficients were used to compare the total score of the QIDS-SR(16) with the total scores of the CDSS, PANSS-subscales and EPS rating scales. RESULTS: In a sample of 621 patients with psychotic disorders, the QIDS-SR(16) showed good internal consistency (α = 0.87). The QIDS-SR(16) correlated moderately with the CDSS (r = 0.44) and the PANSS subscale for emotional distress (r = 0.47). The QIDS-SR(16) showed weak correlation with the PANSS subscale for negative symptoms (r = 0.28) and minimal correlation with EPS rating scales (r = 0.09-0.16). CONCLUSIONS: The QIDS-SR(16) may reliably assess depressive symptoms in patients with psychotic disorders, but its concurrent validity with the CDSS was rather poor in this population. We would recommend developing a new self-report questionnaire for the assessment of depressive symptoms in patients with psychotic disorders. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1186/s12888-014-0247-2) contains supplementary material, which is available to authorized users.